Disruptive Technologies for the Militaries and Security - Lele, Ajey.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book debates and discusses the present and future of Disruptive Technologies in general and military Disruptive Technologies in particular. Its primary goal is to discuss various critical and advanced elucidations on strategic technologies. The focus is less on extrapolating the future of technology in a strict sense, and more on understanding the Disruptive Technology paradigm. It is widely accepted that technology alone cannot win any military campaign or war. However, technological superiority always offers militaries an advantage. More importantly, technology also has a great deterrent value. Hence, on occasion, technology can help to avoid wars. Accordingly, it is important to effectively manage new technologies by identifying their strategic utility and role in existing military architectures and the possible contributions they could make towards improving overall military capabilities. This can also entail doctrinal changes, so as to translate these newtechnologies into concrete advantages.
The Context of Technology -- Disruptive Technology and Innovation -- Artificial Intelligence -- Big Data -- Cloud Computing -- Internet of Things (IoT) -- Blockchain -- Lethal Autonomous Weapons Systems (LAWS) -- Hypersonic Weapons -- 3 D Printing -- Next Generation Genomics -- Inexhaustible Sources -- New Materials -- Disruption and Industry 4.0 -- Technology Control -- Conclusion.
Keywords: Engineering design; Politics and war; Application software; Technological innovations; Technology; History; Science -- Social aspects; Engineering Design; Military and Defence Studies; Computer and Information Systems Applications; Innovation and Technology Management; History of Technology; Science and Technology Studies